Differentiation Capacity of Human Urine-Derived Stem Cells to Retain Telomerase Activity - Shi, Yingai; Liu, Guihua; Wu, Rongpei; Mack, David L.; Sun, Xiuzhi Susan; Maxwell, Joshua; Guan, Xuan; Atala, Anthony; Zhang, Yuanyuan (Frontiers in Cell and Developmental Biology, 2022)
Telomerase activity is essential for the self-renewal and potential of embryonic, induced pluripotent, and cancer stem cells, as well as a few somatic stem cells, such as human urine-derived stem cells (USCs). However, it remains unclear how telomerase activity affects the regeneration potential of somatic stem cells. The objective of this study was to determine the regenerative significance of telomerase activity, particularly to retain cell surface marker expression, multipotent differentiation capability, chromosomal stability, and in vivo tumorigenic transformation, in each clonal population of human primary USCs. In total, 117 USC specimens from 10 healthy male adults (25–57 years of age) were obtained. Polymerase chain reaction amplification of a telomeric repeat was used to detect USCs with positive telomerase activity (USCsTA+). A total of 80 USCsTA+ (70.2%) were identified from 117 USC clones, but they were not detected in the paired normal bladder smooth muscle cell and bone marrow stromal cell specimens. In the 20–40-year age group, approximately 75% of USC clones displayed positive telomerase activity, whereas in the 50-year age group, 59.2% of the USC clones expressed positive telomerase activity. USCsTA+ extended to passage 16, underwent 62.0 ± 4.8 population doublings, produced more cells, and were superior for osteogenic, myogenic, and uroepithelial differentiation compared to USCsTA-. Importantly, USCs displayed normal chromosome and no oncological transformation after being implanted in vivo. Overall, as a safe cell source, telomerase-positive USCs have a robust regenerative potential in cell proliferation and multipotent differentiation capacity.